RETRACTED: A review on mindfulness and nursing stress among nurses - Said, Zaini; Kheng, Goh Lei (COUNS-EDU: The International Journal of Counseling and Education, 2018)
RETRACTION TO:Said, Z., & Kheng, G. L. (2018). A review on mindfulness and nursing stress among nurses. COUNS-EDU: The International Journal of Counseling and Education, 3(1), 1-13. (doi: https://doi.org/10.23916/0020170211740This article has been retracted by Publisher based on the following reason:The Editor of COUNS-EDU: The International Journal of Counseling and Education found the double publication in the article publishing due to article's content similarity published in http://ojs.uma.ac.id/index.php/analitika/article/view/1589.Said, Z., & Kheng, G. L. (2018). A review on mindfulness and nursing stress among nurses. ANALITIKA, 10 (1), 31-45,One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process